Stanniocalcin2, but Not Stanniocalcin1, Responds to Hypoxia in a HIF1-Dependent Manner in the Retina - Ail, Divya; Samardzija, Marijana; Chang, Andy C. M.; Keck, Jadwiga; Reddel, Roger R.; Grimm, Christian (Frontiers in Neuroscience, 2022)
The quest for neuroprotective factors that can prevent or slow down the progression of retinal degeneration is still ongoing. Acute hypoxic stress has been shown to provide transient protection against subsequent damage in the retina. Stanniocalcins – STC1 and STC2 – are secreted glycoproteins that are hypoxia-regulated and were shown to be cytoprotective in various in vitro studies. Hence, we investigated the expression of stanniocalcins in the normal, degenerating and hypoxic retina. We show that the expression of Stc1 and Stc2 in the retina was detectable as early as postnatal day 10 and persisted during aging. Retinal expression of Stc2, but not Stc1, was induced in mice in an in vivo model of acute hypoxia and a genetic model of chronic hypoxia. Furthermore, we show that HIF1, not HIF2, is responsible for regulating Stc2 in cells with the molecular response to hypoxia activated due to the absence of von Hippel Lindau protein. Surprisingly, Stc2 was not normally expressed in photoreceptors but in the inner retina, as shown by laser capture microdissection and immunofluorescence data. The expression of both Stc1 and Stc2 remained unchanged in the degenerative retina with an almost complete loss of photoreceptors, confirming their expression in the inner retina. However, the absence of either Stc1 or Stc2 had no effect on retinal architecture, as was evident from retinal morphology of the respective knockout mice. Taken together our data provides evidence for the differential regulation of STC1 and STC2 in the retina and the prospect of investigating STC2 as a retinal neuroprotective factor.